Agreement between the Open University Worldwide Limited and BRAC University (2009) - Open University Worldwide Limited; BRAC University (Open University Worldwide Limited and BRAC University, 2013)
This Agreement is made on the 12th day of November 2009 of the Christian era. between the Open University Worldwide Limited (a limited company and wholly owned subsidiary of the Open University (hereinafter refereed to as "the OU"), incorporated in England with registration number 1260275) Whose registered office is Walton Hall, Milton Keynes MK7 6AA, United Kingdom (hereinafter referred to as "OUW"; AND BRAC University (a body incorporated in 2001, under the laws of Bangladesh and authorized by the University Grants Commission of Bangladesh) whose registered office is at 66, Mohakhali, Dhaka-1212, Bangladesh (hereafter referred to as "BRACU").